2018
DOI: 10.3233/bmr-171078
|View full text |Cite
|
Sign up to set email alerts
|

Screening of scoliosis in school children in Tehran: The prevalence rate of idiopathic scoliosis

Abstract: Regarding the high rate of scoliosis in our population and approval of this screening test in different studies, routine use of this screening method is highly recommended in schoolchildren. It is cost beneficial and can be effective in prevention and early treatment of scoliosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
5
0
4
Order By: Relevance
“…[66] Scoliosis [67] Rib Hump Angle/Scoliosis [68] Kyphotic Angles [69] Cobb Angle/Thoracic Scoliosis [70] Cobb Angle/Thoracic Scoliosis [71] Lumbar Lordosis [72] Rib Hump Angle/Scoliosis Evaluation [73] Cobb Angle of Thoracolumbar Scoliosis [74] Cobb Angle [75] Cobb Angle [76] Cobb Angle [77] Head, Ribcage, Shoulder, Hip and Knee Tilt [65] Inclination of the Human Spinal Points [78] SS and Lumbar Curve [79] PI, PT and LL [80] Sagittal Curvaures [81] Thoracic Spine Rotation [82] LL, PI, and PT [83] Head, Ribcage, Shoulder, Hip Tilt [84] Head, Ribcage, Shoulder, Hip Inclination [85] Scoliosis Angle [86] Head, Shoulder and Ribcage Tilt [87] Head, Ribcage, Shoulder, Hip and Knee Tilt [88] LL, PI, SS and PT [89] LL, PT, and SS [90] Rib Hump/Scoliosis Evaluation Note: LL = Lumbar Lordosis; PI = Pelvic Incidence; SS = Sacral Slope; PT = Pelvic Tilt.…”
Section: Study Measures Takenmentioning
confidence: 99%
See 2 more Smart Citations
“…[66] Scoliosis [67] Rib Hump Angle/Scoliosis [68] Kyphotic Angles [69] Cobb Angle/Thoracic Scoliosis [70] Cobb Angle/Thoracic Scoliosis [71] Lumbar Lordosis [72] Rib Hump Angle/Scoliosis Evaluation [73] Cobb Angle of Thoracolumbar Scoliosis [74] Cobb Angle [75] Cobb Angle [76] Cobb Angle [77] Head, Ribcage, Shoulder, Hip and Knee Tilt [65] Inclination of the Human Spinal Points [78] SS and Lumbar Curve [79] PI, PT and LL [80] Sagittal Curvaures [81] Thoracic Spine Rotation [82] LL, PI, and PT [83] Head, Ribcage, Shoulder, Hip Tilt [84] Head, Ribcage, Shoulder, Hip Inclination [85] Scoliosis Angle [86] Head, Shoulder and Ribcage Tilt [87] Head, Ribcage, Shoulder, Hip and Knee Tilt [88] LL, PI, SS and PT [89] LL, PT, and SS [90] Rib Hump/Scoliosis Evaluation Note: LL = Lumbar Lordosis; PI = Pelvic Incidence; SS = Sacral Slope; PT = Pelvic Tilt.…”
Section: Study Measures Takenmentioning
confidence: 99%
“…PostureScreen proved to be a useful tool for dentists in the early diagnosis of dental occlusion pathology. [85] Mean, SD, Student's t-distribution, ANOVA and Fisher's exact test for detecting scoliosis in school children.…”
Section: Measures Of Spinal Curvatures With Both Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Moalej ve ark., geliştirdikleri skolyoz tarama yazılımı ile yaş aralığı 7-12 yıl olan 144 öğrenciyi vertebral muayeneden geçirmişler ve skolyoz görülme sıklığını literatürün çok üstünde, %4,86 olarak hesaplamışlardır. 34 Weiss ve ark., yaşlarına göre dört gruba ayırarak Schroth metodu ile tedavi ettikleri İS'li hastalarda, göğüs genişliğindeki ortalama artış oranının bütün gruplar için %20'den fazla olduğunu belirlemişlerdir. 35 LeBlanc ve ark.…”
Section: Skolyoz Ve Antropometri̇k öLçümler Arasindaki̇ İli̇şki̇unclassified
“…A systematic review of 20 studies performed between 1977 and 2011 found a prevalence rate of scoliosis among schoolchildren ranging from 1% to 14.8% [4]. A recent study in Iran published in 2018 found a prevalence of clinical scoliosis of 10.4% among schoolchildren [5]. A local study in Abha City found a higher prevalence rate of 19.1% among adolescents [6].…”
Section: Introductionmentioning
confidence: 99%